Challenges and priorities for climate‐informed invasive species management across multiple scales - Annette E. Evans; Laura Brewington; Carrie Brown‐Lima; Emily Fusco; Rachel M. Gregg; Deah Lieurance; Elliott W. Parsons; R. Chelsea Nagy; Lindsey Thurman; Toni Lyn Morelli (Conservation Science and Practice)
Abstract In recent decades, substantial evidence has accumulated regarding the effects of climate change on the establishment, spread, and impact of invasive species. While the importance of incorporating climate change into invasive species management and policy is increasingly recognized, practitioner experiences and perspectives are often overlooked. Consequently, invasive species research may be misaligned with the needs of managers and the threats of climate change. Here, we compare survey responses from a boundary‐spanning organization, the Regional Invasive Species and Climate Change (RISCC) Management Network, to identify common priorities and challenges in managing invasive species in a changing climate in the United States. Survey respondents reported that 22% of management and research time is dedicated to emerging invasive species threats. Common barriers to climate‐informed invasive species management include limited time, funding, and personnel. Understanding how climate change may impact control strategies was consistently identified as a high priority for invasive species management, followed by identifying resilient ecosystems and range‐shifting taxa. These results demonstrate the critical need for stronger researcher‐practitioner networks and greater investment in research and policy topics that more closely align with management needs to address the interacting stressors of invasive species and climate change.